The Nuts and Bolts of PIN Auxin Efflux Carriers - Zwiewka, Marta; Bilanovičová, Veronika; Seifu, Yewubnesh Wendimu; Nodzyński, Tomasz (Frontiers in Plant Science, 2019)
The plant specific proteins named PIN efflux carriers facilitate the directionality of auxin flow and thus play a vital role in the establishment of local auxin maxima within plant tissues that subsequently guide plant ontogenesis. They are membrane integral proteins with two bundles of alpha helical regions linked with a hydrophilic loop domain which is usually longer for the plasma membrane localized PINs and harbors molecular ques important for the subcellular localization and thus auxin efflux function of those transporters. The three-dimensional structure of PIN has not been solved yet. However, there are scattered but substantial data concerning the functional characterization of amino acid strings that constitute those carriers. Those sequences include motifs vital for vesicular trafficking, residues regulating membrane diffusion, cellular polar localization and activity of PINs. Here we summarize those bits of information striving to provide reference to structural motifs that have been investigated experimentally hoping to stimulate the efforts towards unravelling of PIN structure-function connections.